Utilization of Katuk (Sauropus androgynus L Merr) meal and extract as ration substitution to produce low chollesterol Japanese Quail product - Subekti, Sri; Piliang, Wiranda G; Manalu, Wasmen; Murdiati, Tri Budhi (Indonesian Journal of Animal and Veterinary Sciences, 2006)
Katuk (Sauropus androgynus L Merr) is known to contain carotenoids, vitamin E, vitamin C, protein and phytosterol compound. This study was aimed to determine the ability of phytosterols in Sauropus androgynus (SA) leaf to obtain poultry product that has low cholesterol content. One hundred fifty female quails were raised from 2-27 weeks old, divided into three treatment diets, five replicates with 10 quails in each replicate. The treatment diets were: 1) Control group: diet without katuk leaf meal; 2) Diet with 9% SA ethanol 70% extract (SAE); 3) Diet containing 9% SA meal (SAM). Kolesterols were determined with CHOD-PAP-Method by Human, there is enzymatic Colorimetric Test for Cholesterol with Lipid Clearing Factor. The result showed that total cholesterol in the egg yolk, carcass and liver of SAE and SAM treated quails were lower (P<0.05) than that of the control-treated quails, except the cholesterol content in the serum. These findings indicated that the cholesterol concentration of female quails was decreased due to phytosterol content in katuk leaf. Key Words: Phytosterol, Katuk Leaf, Kolesterol, Quails